Epidemiological, clinical, and echocardiographic features of twenty 'Takotsubo-like' reversible myocardial dysfunction cases with normal coronarography following immersion pulmonary oedema. Issue 3 (4th May 2021) - Demoulin, Raphaël; Poyet, Raphaël; Castagna, Olivier; Gempp, Emmanuel; Druelle, Arnaud; Schmitt, Paul; Capilla, Eléonore; Rohel, Gwénolé; Pons, Frédéric; Jégo, Christophe; Brocq, François-Xavier; Cellarier, Gilles R.
Abstract: Background: Pulmonary immersion oedema is a frequent diving accident. Although its outcome is generally favourable within 72 h, it can nonetheless lead to heart failure or sudden death. Cases of transient myocardial dysfunction have been reported in the literature. This phenomenon is similar to Takotsubo syndrome in many ways. It is characterised by transient myocardial hypokinesia, without associated coronary lesions. Methods: We report on 20 cases of patients who showed transient alteration of left ventricular kinetics with normal coronary angiography over the course of an immersion pulmonary oedema. Results: The echocardiographic localisation of the myocardial damage was generally focal and not centred on the apex with an average left ventricular ejection fraction of 45%. The main anomalies in the electrocardiographic repolarisation were T wave inversion with corrected QT interval prolongation. We also observed a moderate increase in troponin levels, with discordance between the enzymatic peak and the severity of the left ventricle segmental dysfunction. Conclusion: These cases suggest the incidence of a clinical entity strongly reminiscent of Takotsubo phenomenon of atypical topography as a consequence of diving accidents.